2012
DOI: 10.1155/2012/576086
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive, Anti-Inflammatory, and Antipyretic Activity of Mangrove Plants: A Mini Review

Abstract: Mangrove plants are specialised plants that grow in the tidal coasts of tropic and subtropic regions of the world. Their unique ecology and traditional medicinal uses of mangrove plants have attracted the attention of researchers over the years, and as a result, reports on biological activity of mangrove plants have increased significantly in recent years. This review has been set out to compile and appraise the results on antinociceptive, anti-inflammatory, and antipyretic activity of mangrove plants. While t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…From many of the ethnomedicinal uses of the genus, the widest applications have been in the treatment of rheumatism, pregnancy, ulcer and smallpox (Bandaranayake 2002). Different parts of the plant such as leaf, bark/stem, seeds, roots and fruits have been exploited over the years for the treatment of various diseases (Shilpi et al 2012;Simlai & Roy 2013). Plants like Avicennia alba Blume (a variant to A. marina), A. marina, A. nitida and A. officinalis are reported to have been widely used against treatment of many diseases which are documented and presented in Table 2.…”
Section: Ethnomedicinal Usesmentioning
confidence: 99%
“…From many of the ethnomedicinal uses of the genus, the widest applications have been in the treatment of rheumatism, pregnancy, ulcer and smallpox (Bandaranayake 2002). Different parts of the plant such as leaf, bark/stem, seeds, roots and fruits have been exploited over the years for the treatment of various diseases (Shilpi et al 2012;Simlai & Roy 2013). Plants like Avicennia alba Blume (a variant to A. marina), A. marina, A. nitida and A. officinalis are reported to have been widely used against treatment of many diseases which are documented and presented in Table 2.…”
Section: Ethnomedicinal Usesmentioning
confidence: 99%
“…Because of the scant distribution of the mangrove forests, mangrove plant species are still almost unacquainted to a vast population. Ancient people used mangrove plant species scarcely, because they could hardly enter these areas (Shilpi et al, ). Heritiera fomes Buch.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the crude extract from the bark of Rhizophora mangle was shown to have significant gastroprotective activity (Berenguer et al, 2006), and the ethanol extract of the leaves of Ceriops decandra was reported to have antinociceptive activity (Shilpi et al, 2012). The Rhizophoraceae species Rhizophora mucronata and Ceriops tagal are used in herbal medicine to control diabetes, and in vitro screening of the 80% aqueous ethanolic extracts from the bark of these species revealed high activity against a-glucosidase, with IC 50 values of 0.08 AE 1.82 and 0.85 AE 1.46 mg/mL, respectively (Lawag et al, 2012).…”
Section: Introductionmentioning
confidence: 99%